The Buddhist Methods Promotion In Preventing The Recidivism Among Drug Prisoners Of Lamphun Provincial Prison - Sonti, Isarapong (MCU Haripunchai Review, 2025)
The research on Buddhist practices to promote the prevention of recidivism among drug offenders in Lamphun Provincial Prison aims to 1) study the conditions of recidivism prevention and the implementation of the prevention of recidivism among drug offenders 2) study the process of promoting recidivism prevention among drug offenders 3) propose the use of Buddhist practices to promote the prevention of recidivism among drug offenders in Lamphun Provincial Prison. The qualitative research used in-depth interviews with 20 specifically selected key informants, with a consistency index of 0.60-1.00, which is consistent with the objectives. The research results found that: 1) The conditions for preventing recidivism among drug offenders found that drug problems were addressed by constantly monitoring safety; social problems were addressed by changing social living conditions; economic problems were addressed by providing career opportunities; and other problems were addressed by continuous assistance. 2) The process of promoting recidivism prevention among drug offenders found that opportunities were provided by supporting education; mental development was addressed by restoring mental health; and vocational training was provided by providing a variety of vocational training. In terms of rehabilitation through life and career skills development 3) Buddhist practices promote the prevention of recidivism among drug offenders in Lamphun Provincial Prison. It was found that in terms of truth, there was a commitment to not committing crimes again; in terms of self-control, there was a policy to promote quality of life and mind; in terms of patience, there was a mental training project; and in terms of giving, there was the development of activities to create a sense of volunteerism.